Neurofibromatosis type 1‐related pseudarthrosis: Beyond the pseudarthrosis site. Issue 10 (18th June 2019) - Brekelmans, Carlijn; Hollants, Silke; De Groote, Caroline; Sohier, Natalie; Maréchal, Marina; Geris, Liesbet; Luyten, Frank P.; Ginckels, Lieve; Sciot, Raf; de Ravel, Thomy; De Smet, Luc; Lammens, Johan; et al.
Abstract: Neurofibromatosis type 1 (NF1) is an autosomal dominant disorder affecting approximately 1 in 2, 000 newborns. Up to 5% of NF1 patients suffer from pseudarthrosis of a long bone (NF1‐PA). Current treatments are often unsatisfactory, potentially leading to amputation. To gain more insight into the pathogenesis we cultured cells from PA tissue and normal‐appearing periosteum of the affected bone for NF1 mutation analysis. PA cells were available from 13 individuals with NF1. Biallelic NF1 inactivation was identified in all investigated PA cells obtained during the first surgery. Three of five cases sampled during a later intervention showed biallelic NF1 inactivation. Also, in three individuals, we examined periosteum‐derived cells from normal‐appearing periosteum proximal and distal to the PA. We identified the same biallelic NF1 inactivation in the periosteal cells outside the PA region. These results indicate that NF1 inactivation is required but not sufficient for the development of NF1‐PA. We observed that late‐onset NF1‐PA occurs and is not always preceded by congenital bowing. Furthermore, the failure to identify biallelic inactivation in two of five later interventions and one reintervention with a known somatic mutation indicates that NF1‐PA can persist after the removal of most NF1 negative cells.